Climate change and agriculture in Bangladesh: impacts and adaptation strategies: Climate Change and Agricultural Adaptation in Bangladesh - Sheikh, M M; Pervez, A K M K (Bangladesh Journal of Agriculture, 2025)
The interrelationship between climate change and agriculture has been widely studied in Bangladesh. Bangladesh is predominantly an agricultural nation where farming is highly dependent on natural conditions such as temperature, rainfall, soil quality, and water availability. However, Bangladesh frequently faces extreme climatic events, including droughts and floods, which are further exacerbated by global climate change, threatening agricultural productivity and food security. This study employs a bibliometric approach to critically analyze existing academic literature on climate change and agricultural adaptation in Bangladesh. The primary objectives of the study are to (1) assess the impact of climate change on Bangladesh agriculture and (2) evaluate the effectiveness of current adaptation strategies. Data were sourced from Scopus, yielding 1,052 relevant documents, including 765 scholarly articles. VOSviewer software was used to map bibliometric connections, highlight key authors, and extract insights from journals and other sources. The study revealed that there are inconsistencies between agricultural policies and climate change adaptation strategies. To bridge this gap, the study recommends policy improvements, including targeted subsidies and pricing mechanisms that encourage farmers to adopt location-specific adaptation strategies, enhancing climate resilience in agriculture. Bangladesh J. Agri. 2025, 50(1): 132-148